Mixed Small Cell Neuroendocrine Carcinoma and High-grade Urothelial Carcinoma with Sarcomatoid Differentiation Coexisting with (Primary/Metastatic) Melanoma of the Urinary Bladder: A Case Report - Chatnetiwut, Kamonchanok (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2026)
Both mixed neuroendocrine non-neuroendocrine neoplasms and melanomas of the urinary bladder are rare, and the coexistence of these neoplasms is extremely rare. This case report highlights a 77-year-old male who presented with gross hematuria for the past 1 week. Transurethral resection of bladder tumor was performed and the resected tissue was sent for histopathology, which revealed mixed (1) small cell neuroendocrine carcinoma with a minor component of high-grade urothelial carcinoma with focal sarcomatoid differentiation and (2) melanoma (primary bladder melanoma is considered after exclusion of metastasis). This case highlights the critical role of meticulous histopathological evaluation in bladder tumors, as rare and aggressive neoplasms may coexist and require accurate diagnosis for appropriate management. Keywords: mixed neuroendocrine non-neuroendocrine neoplasm (MiNEN); small cell neuroendocrine carcinoma; high-grade urothelial carcinoma; bladder melanoma; collision tumor; bladder neoplasms; case report.